2012
DOI: 10.1371/journal.pone.0032082
|View full text |Cite
|
Sign up to set email alerts
|

Scopolamine Administration Modulates Muscarinic, Nicotinic and NMDA Receptor Systems

Abstract: Studies on the effect of scopolamine on memory are abundant but so far only regulation of the muscarinic receptor (M1) has been reported. We hypothesized that levels of other cholinergic brain receptors as the nicotinic receptors and the N-methyl-D-aspartate (NMDA) receptor, known to be involved in memory formation, would be modified by scopolamine administration.C57BL/6J mice were used for the experiments and divided into four groups. Two groups were given scopolamine 1 mg/kg i.p. (the first group was trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 87 publications
3
47
0
Order By: Relevance
“…impairments, which typically use 100 μg/kg to 3 mg/kg doses of scopolamine (31)(32)(33). Second, the antidepressant-like effects were observed 24 hours after the final 25 μg/kg dose of scopolamine, at a time when the drug had largely been cleared.…”
Section: Figure 6 M1-achr Mediates Cholinergic Stimulation Of Sst Inmentioning
confidence: 99%
“…impairments, which typically use 100 μg/kg to 3 mg/kg doses of scopolamine (31)(32)(33). Second, the antidepressant-like effects were observed 24 hours after the final 25 μg/kg dose of scopolamine, at a time when the drug had largely been cleared.…”
Section: Figure 6 M1-achr Mediates Cholinergic Stimulation Of Sst Inmentioning
confidence: 99%
“…As a standard amnesic drug, scopolamine is frequently used in similar 50 was not established, the therapeutic dose was approximated from a previous study 36 . studies [32][33][34][35] . In this study, scopolamine was successfully substituted by another non-selective muscarinic receptor antagonist -QNB.…”
Section: Discussionmentioning
confidence: 99%
“…This approach enabled long-term observation of anti-cholinergic effects due to the prolonged action of QNB compared to scopolamine 27,36 . To evaluate the pro-cognitive effects of novel compounds, the multiple T-maze test was selected 26,34,37,38 . This behavioural task reflects spatial learning and memory, requiring recollection of spatial information and the construction of a cognitive map, which is considered to be analogous to human episodic memory in animals 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Scopolamine appears to be a non-selective muscarinic receptor antagonist; it has been demonstrated that scopolamine has a high selectivity for the muscarinic receptor, although it has also been reported that high doses of scopolamine are also blocking nicotinic receptors [18].…”
Section: Discussionmentioning
confidence: 99%